Indoor mould exposure, asthma and rhinitis: findings from systematic reviews and recent longitudinal studies. (16th May 2018) - Caillaud, Denis; Leynaert, Benedicte; Keirsbulck, Marion; Nadif, Rachel
Starting from the Institute of Medicine (IOM) and World Health Organization (WHO) reports, this review provides an overview of the literature published from 2006 to 2017 on the associations between indoor mould exposure and asthma and rhinitis separately in children and adults with a focus on longitudinal epidemiological studies. A systematic search of peer-reviewed literature was performed, including systematic reviews and meta-analyses, longitudinal, incident case–control and panel studies. 61 publications were identified reporting visible mould or mould odour or quantitative assessment of culturable fungi or mould species. In children, visible mould and mould odour were associated with the development and exacerbations of asthma, providing sufficient evidence of a causal relationship. Results from population-based studies in adults were too few and divergent to conclude at more than a limited level of evidence. Exposure to mould in a work building was associated with the incidence and exacerbations of occupational asthma, and we concluded at a sufficient evidence for an association. Systematic reviews, meta-analyses and longitudinal studies on the relationships between mould exposure and allergic rhinitis provide sufficient evidence of an association. This review extended the conclusions of the IOM and WHO reports, and highlighted the need for further longitudinal studies on asthma in adults, and on rhinitis. Evidence that indoor mould at home increases asthma in children is accumulating but is still insufficient in adults http://ow.ly/nEnt30j7lco